Anne of France : lessons for my daughter - Anne, of France, 1461-1522 (Library of medieval women., 2004)
Anne of France (1461-1522) composed these lessons - presented as a portrait of an ideal princess - as guidance in negotiating the pitfalls facing a woman in the world of politics.